Antitumor effects of a covalent cyclin-dependent kinase 7 inhibitor in colorectal cancer. Issue 5 (June 2019) - Wang, Jian; Li, Zhenyu; Mei, Hong; Zhang, Dejun; Wu, Gang; Zhang, Tao; Lin, Zhenyu
Abstract : Although both antiepidermal growth factor receptor and vascular endothelial growth factor therapies have been shown to be effective against colorectal cancer (CRC), their beneficial effects are limited to a small proportion of patients and are not sustainable. Cyclin-dependent kinase 7 (CDK7) is an important regulator of the transcriptional machinery. Use of small-molecule inhibitors of the transcriptional machinery has shown promising selectivity for cancer cells and potent antiproliferative effects. In this study, the effects of a covalent CDK7 inhibitor THZ1 as a potent anti-CRC compound were evaluated in vitro and in vivo . THZ1 significantly inhibited cell growth and induced apoptosis of CRC cells in vitro . In addition, it also decreased xenograft tumor growth in vivo . RNA-Seq showed that THZ1 induced inhibition of a number of oncogenic transcripts. Taken together, our results indicate that pharmacological modulation of CDK7 kinase activity by THZ1 may represent a potential strategy in the treatment of CRC. Abstract : Supplemental Digital Content is available in the text.